2011
DOI: 10.1260/1747-9541.6.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Deception, Individual Differences and Penalty Kicks: Implications for Goalkeeping in Association Football

Abstract: The purpose of the current article is to review findings from the visual anticipation literature with a particular focus on penalty kick goalkeeping in Association football. We give a brief introduction to the area of research before providing reviews of two recent studies. First, we focus on the applied implications of a study that examined the effect of deception and non-deception penalty kick strategies on goalkeeping performance. Second, we consider further limiting factors on the accuracy of goalkeeper vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
(25 reference statements)
1
28
0
2
Order By: Relevance
“…In light of the above, whilst the timing in which goalkeepers rely on for essential information during a penalty kick is consistent between studies (Button et al, 2011;Dicks et al, 2011;Savelsbergh et al, 2005), the essential location of obtaining these visual information appears to be inconclusive for goalkeepers (i.e., which body segments of the penalty taker?). This inconsistency in findings may be attributed to studies only temporally occluding video simulations with the use of an eye-tracking device (Franks & Harvey, 1997;Savelsbergh et al, 2005Savelsbergh et al, , 2002.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In light of the above, whilst the timing in which goalkeepers rely on for essential information during a penalty kick is consistent between studies (Button et al, 2011;Dicks et al, 2011;Savelsbergh et al, 2005), the essential location of obtaining these visual information appears to be inconclusive for goalkeepers (i.e., which body segments of the penalty taker?). This inconsistency in findings may be attributed to studies only temporally occluding video simulations with the use of an eye-tracking device (Franks & Harvey, 1997;Savelsbergh et al, 2005Savelsbergh et al, , 2002.…”
Section: Introductionmentioning
confidence: 65%
“…Therefore, information such as the direction, speed and timeto-contact of a moving ball, all of which can only be determined once the ball has been kicked, may be of no benefit to the goalkeeper (Diaz, Fajen, & Phillips, 2012;Regan, 1997). In fact, research has consistently shown that the most important visual cues to correctly anticipate the direction of the ball for goalkeepers are from events immediately prior to the striker's kicking action to the striker's foot-to-ball contact (Button, Dicks, Haines, Barker, & Davids, 2011;Dicks, Uehara, & Lima, 2011;Savelsbergh, Van Der Kamp, Williams, & Ward, 2005). However, studies using eye-tracking devices have reported that fixations on the torso, hips and kicking leg of the striker result in successful anticipation of a penalty kick (Lopes, Araújo, & Davids, 2014;Savelsbergh, Williams, Van Der Kamp, & Ward, 2002) although Franks and Harvey (1997) and Savelsbergh and colleagues (2005) have shown that anticipatory skills of goalkeepers were more successful when fixating on the stance leg (i.e., non-kicking leg) prior to foot-to-ball contact.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important for team sports that dominate among students. Training and competitive activities within team sports require intensive development of general and speed endurance, reaction rapidity, due to huge amount of information processed fast under the time pressure in a continuously changing situation (Dicks et al, 2011;Drid et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time the central nervous system is the main element of the hierarchical structure of functional systems providing the adaptation of the body Perez et al, 2013). The problem of influence made by physical activities on the functional state within the nervous system is one of the central problems in studying patterns and adaptation of the body to the effects of physical and sport activity (Dicks et al, 2011;Friston, 2012). The level of lability and mobility of nervous processes, rate of muscle component reaction determine physiological reserves and rapidity development quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation